2016
DOI: 10.1007/s00170-016-8708-z
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of chatter stability in high speed milling using the numerical differentiation method

Abstract: A numerical differentiation method is presented to predict the high speed milling stability of a two degrees of freedom (DOF) system based on the finite difference method and extrapolation method. The milling dynamics taking the regenerative effect into account are represented as linear periodic delayed differential equations (DDE) in the state space form. Then, each component of the first derivative of the state function versus time at the discretized sampling grids is approximated as a weighted linear sums o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…the trapezoidal NIM (Trap-NIM) [31], and the Simpson NIM (Simp-NIM) [34]. The convergence rate and stability lobe diagrams via the single-DOF and two-DOF milling systems are calculated by using these calculated methods.…”
Section: Comparison and Verificationmentioning
confidence: 99%
See 1 more Smart Citation
“…the trapezoidal NIM (Trap-NIM) [31], and the Simpson NIM (Simp-NIM) [34]. The convergence rate and stability lobe diagrams via the single-DOF and two-DOF milling systems are calculated by using these calculated methods.…”
Section: Comparison and Verificationmentioning
confidence: 99%
“…Subsequently, based on the Simpson integration formula, the Simpson method was developed to analyze the stability of milling operation, whose convergence rate was faster than the first-order SDM and second-order FDM [33]. A numerical differentiation method based on the Taylor series expansion was presented to predict the chatter stability as well [34]. According to the linear multistep method, the Milne-Simpson-based-corrector method was investigated to improve the calculated performance [35].…”
Section: Introductionmentioning
confidence: 99%
“…Dai et al [37] presented a milling stability prediction method using the precise integration method. By approximating the differential term of the DDE, several methods were proposed for milling stability analysis, such as the differential quadrature method [38], the numerical differentiation method [39], and the Chebyshev-wavelet-based method [40]. Based on the numerical solution of ordinary differential equations, Qin et al presented the Adams-Moulton-based method (AMM) [41] and the Adams-Simpson-based method (ASM) [42].…”
Section: Introductionmentioning
confidence: 99%
“…en, on the framework of FDM, Ding et al [8] introduced the second-order FDM (2nd FDM), Guo et al [9] proposed the third-order FDM (3rd FDM), and Ozoegwu reported the least squares approximation methods [10] and hyper-thirdorder full-discretization methods [11]. Besides, the numerical integration method [12] and differential quadrature method [13] developed by Ding and his coworkers, the Runge-Kutta-based methods proposed by Niu et al [14], the improved precise integration method proposed by Li et al [15], the Simpson-based method presented by Zhang et al [16], numerical differentiation method reported by Zhang et al [17], and so on are proposed for the stability prediction in the milling process. More recently, Olvera et al [18] presented the stability analysis for a single degree of freedom down-milling operation in a thin-walled workpiece by using the enhanced multistage homotopy perturbation (EMHP) method.…”
Section: Introductionmentioning
confidence: 99%